IDENTIFIKASI KERUSAKAN BANGUNAN GEDUNG GEREJA JEMAAT GPM SOLA SCRIPTURA BANDA PASCA GEMPA DI DUSUN AMALATUEI NEGERO SULI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Pattiasina, Paulles Geovani; Roberth, Herry Henry; Tuanakotta, Abraham (Jurusan Teknik Sipil, 2024)
Indonesia is in an area with quite high earthquake activity because this high level of activity can damage important facilities and infrastructure. After the earthquake on September 26 2019 with a magnitude of 68, it caused shaking in several areas in Maluku. The epicenter of the earthquake was located on Seram Island, causing a lot of damage to both infrastructures. Residents' houses and worship facilities, including the GPM Sola Suptura Banda Congregational Church Building, suffered quite severe damage, both structural and non-structural. The aim of writing this thesis is to obtain identification results based on the level of damage that occurred. In this research, a survey and direct inspection were carried out which will be analyzed or processed based on an assessment of the level of damage that occurred at the location. From the identification results, the overall level of damage to the building reached 74%, which means the condition of the building was completely damaged. The earthquake factors classified according to each structural component are structural damage to columns by 5%, beams by 16% and also damage to construction, roof by 4%, ceiling by 12%, walls by 19%, utilities by 7%, sexta finishing of 5%, which results in a weight percentage of the entire building being 74%, which means the condition of the building is in the Total Damaged (RT) category because it is 65%, according to Minister of Public Works Regulation No. 24/PRT/M/2008.